MENGGALI DAMPAK REVOLUSI MEDIA SOSIAL TERHADAP INDUSTRI HALAL DI INDONESIA - Oktaviany, Mega; Hasbalah, Fikri Zaeni (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2023)
The objective of this research is to examine the impact of the social media revolution on the halal industry in Indonesia. The emergence of social media has transformed the way consumers interact and communicate. This study employs a qualitative descriptive methodology with literature review as the data source. The findings reveal that through social media, the halal industry can expand its promotional reach, enhance customer engagement, and build strong relationships with a wider audience. Social media also plays a significant role in promoting and raising awareness about halal products and services in Indonesia. By leveraging relevant and attention-grabbing content, and sharing valuable information, businesses can influence consumer perceptions and decisions regarding the halal industry. Through the social media revolution, consumers also have easy access to search for information, reviews, and recommendations before choosing halal products or services. Therefore, effective and relevant marketing strategies should be implemented by the halal industry in Indonesia, keeping up with the latest social media trends. By harnessing the power of the social media revolution, the halal industry in Indonesia can continue to thrive, achieve sustainable growth, and become a leader in the global halal market.